Update on cryptogenic organizing pneumonia - Radzikowska, Elzbieta; Fijolek, Justyna (Frontiers in Medicine, 2023)
Cryptogenic organizing pneumonia (COP) is a form of idiopathic interstitial pneumonia that results from the pulmonary reaction to various unidentified injuries. Secondary organizing pneumonia is diagnosed when the triggering factor has been identified; it is mainly caused by infections, toxic substance exposure, drugs, connective tissue diseases, malignancies, autoimmune diseases, bone marrow or organ transplantation, and radiotherapy. There has been an increase in the number of reports of drug-induced organizing pneumonia (OP). New biological therapies, interferon, monoclonal antibodies, anti-interleukin antibodies, and PD1/PDL-1 inhibitors may induce this specific pulmonary reaction. The classical form of COP is usually subacute and does not manifest as severe disease. Patients maintain sufficient respiratory function, and treatment with steroids is usually effective. Several specific forms of OP (e.g., the cicatricial variant or acute fibrinous type) have distinct clinical and histological features, require higher doses of immunosuppressive drugs, and have a worse prognosis. In the era of administering steroid-sparing therapies for the treatment of interstitial lung diseases, connective tissue diseases, and other conditions, it is important to emphasize this type of therapy for patients with COP.